Reducing Energy Consumption, Increasing Wear, Maximizing Output By Producing Wear Parts With New Alloys Or Combining Traditional Alloys And Ceramic Materials - SME Annual Meeting 2023 - T. Veneroso (Society for Mining, Metallurgy & Exploration, 2023)
Comminution is the process by which rock or ore is reduced to a size where the liberation of the minerals is maximized without changing the chemical or physical properties of the rock. Comminution accounts for about 50% of all energy that mines use (Klein et al., 2018). Growing demands from stakeholders and shareholders for sustainable development and CO2 reduction will increase the need for energy-efficient comminution. Ores with different mineralogical characteristics, textures, strengths, apparent stiffness, and mass-specific fracture energies need to be processed with a specific, new, and efficient comminution technology to increase the production and profitability of mining companies. The adoption of crusher wear parts built with new materials, such as non-Hadfield manganese steel or synthetic materials or traditional manganese with wear-resistant components, could improve the efficiency of the crushers, reduce downtime, increase production, improve the desired P80 (the aperture through which 80% of the product will pass) product size distribution, and enhance mine safety.